Are You Doing Your Part?: Veterans' Political Attitudes and Heinlein's Conception of Citizenship. (October 2014) - Klingler, Jonathan D.; Chatagnier, J. Tyson
Drawing from the concept of citizenship in the novel, Starship Troopers, we consider public opinion in a world in which "service guarantees citizenship." We do this by examining the political attitudes of US (volunteer) veterans—a group generally neglected in the public opinion literature—relative to the adult population at large. Using data from the 2006 Cooperative Congressional Election Study, we demonstrate that, as a group, veterans tend to be more ideologically conservative and more likely to identify as Republican than their nonveteran counterparts. This finding holds for both individual issues and self-identification.